Management of Computer Vision Syndrome with Saindhava Jala Seka and Triphala Ghritapana - A Case Study - Borkar Manasi R,; Kotangale Sumedha Y,; Kotangale Yogesh T, (AYUSHDHARA, 2021)
Computer vision syndrome (CVS) is a symptom complex in which symptoms develop due to long screening time and improper postures while using computers. Ayurveda has mentioned Shushkakshipaka under Sarvagat Netra Roga. The symptoms of CVS and Shushkakshipaka when corelated, it denotes imbalance of Vata and Pitta Dosha. These vitiated Doshas carried by Siras to the eyes. When Doshas accumulated in eye the condition develops, called as Shushkakshipaka. Over use of Internet, Computers, Electronic devices increasing the risk factors about maintaining the normal vision. For the management of the CVS case, the Saindhava Jala Seka and Abhyantara Triphala Ghritapana is chosen from Sushrut Samhita. Triphala Ghrita is beneficial for complete maintenance of physiology of eye. The Guna Karma of Saindhava and Triphala Ghrita are Vata-Pitta Shamaka and both having Chakshushya properties. The main purpose for this study is to find safe and effective treatment without untoward effect in the management of CVS along with respective ergonomics advice. The required clinical tests done to observe the effectiveness of the combination of local and systemic treatment. The dryness in the eyes and associated symptoms can be resolved with the local treatment like Seka. Both the treatment modalities in combination have potential to give local and systemic relief improving the symptoms of CVS.